Peningkatan Kreatifitas Melalui Funcooking pada Kelompok A RA Az Zahra Kebayoran Baru Jakarta Selatan - Dwi Puji Lestari (Universitas Trunojoyo Madura, 2019)
The purpose of this research is how to increase creativity through fun cooking in group A RA Az Zahra Kebayoran Baru South Jakarta. This study was carried out in 4-5 years old group A children of 16 children. This research is an action research with Kemmis and Taggart model which consists of 4 stages namely (plan, action, observation and reflection). This study consisted of 2 cycles, with each cycle as many as 8 meetings. Data collection techniques are using observation, field notes, and documentation. Data analysis uses quantitative and qualitative. Quantitative data analysis is carried out with statistical descriptions to compare pre cycles to cycles II. The stages of qualitative analysis are data reduction, data display and verification. The results showed that there was an increase in creativity through the method of fun cooking. The results of the study in cycle I, and cycle II, the results of which increased significantly from before the action only 37.5% of the number of children in the class increased to 81% in cycle 2. The average value of the percentage in the pre-action was 33.20%; cycle 1 is 59.76% and cycle 2 is 84.375%. The increase from cycle 1 to cycle 2 reached 24.615%.